Keterkaitan Lembaga Keuangan Mikro (LKM), Usaha Mikro dan Kecil (UMK) serta Kemiskinan di Indonesia Tahun 2012 - Suhartini, Atik Mar’atis; Yuta, Ropika (Jurnal Ekonomi Kuantitatif Terapan, 2015)
One approach to reduce poverty is through microfinance, as a source of flexible financing for micro and small enterprises (UMK). This study aims to determine the relationshipbetween BPR, UMK and poverty in Indonesia 2012. This study used secondary data from 33 provinces with descriptive analysis and path analysis method. The results shows that the presence of BPR and UMK can help poverty alleviation. The influence of BPR will stronger in poverty reduction when working through of UMK.
Keywords: BPR; UMK; poverty